Novel design of micropump based on multi-angle paper-based capillary approach for enhanced and well-controlled flow rates - Bahbibi Rahmatullah (Tanjung Malim, 2023)
Novel design of micropump based on multi-angle paper-based capillary approach for enhanced and well-controlled flow rates by Bahbibi Rahmatullah